Maintenance of Professional Boundaries and Family Involvement in Residential Aged Care. (September 2019) - Omori, Maho; Baker, Courtney; Jayasuriya, Jude; Savvas, Steven; Gardner, Anastasia; Dow, Briony; Scherer, Sam
The importance of family's involvement in care planning has been stressed to cater individualized, person-centered care in residential aged care. However, in reality, there are numerous structural obstacles and barriers that limit opportunities for their involvement. The aim of this article is to explore what they are. The findings based on the 12 focus groups, six groups of care professionals and six groups of family/relatives, reveal that the narrow pathway of communication between staff and families, which is hierarchically structured, one-directional, and clinically driven, enables the former to maintain and control professional boundaries between formal and informal care-giving. Such communication style delimits an opportunity for families to engage in quality discussion about care planning for their loved ones with care staff. Communication within residential aged care facilities embodies complex dynamics of care expectations and responsibilities held by care staff and families.